Paint pretreatment method for automobile body and automobile body
Patent Information
- Application Number
- JP2021060181
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-31
- Publication Date
- 2025-02-27
- Estimated Expiration
- 2041-03-31
AI Technical Summary
【0010】 本発明によれば、塗装後の好ましい耐食性が得られる、高張力鋼板を含む自動車車体の塗装前処理方法を提供できる。
Smart Images

Figure 0007636939000001 
Figure 0007636939000002 
Figure 0007636939000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for pre-treatment of an automobile body for painting and to an automobile body. [Background technology]
[0002] Conventionally, when cathodic electrodeposition coating or powder coating is applied to the surface of a metal substrate of an automobile body, the surface of the metal substrate is subjected to a chemical conversion treatment in advance for the purpose of improving corrosion resistance, coating adhesion, etc. In recent years, chemical conversion treatment using zinc phosphate, which does not contain chromium, has been widely used.
[0003] Chemical conversion treatment using zinc phosphate has problems such as difficult wastewater treatment due to the high reactivity of the treatment agent, generation of sludge, and a large environmental load. Therefore, a chemical conversion treatment agent comprising at least one selected from the group consisting of zirconium, titanium, and hafnium, fluorine, and a water-soluble resin has been proposed (for example, see Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2004-218074 A Summary of the Invention [Problem to be solved by the invention]
[0005] The technology disclosed in Patent Document 1 can perform good chemical conversion treatment on metals such as iron, zinc, and aluminum. On the other hand, high-tensile steel sheets used in automobile bodies are lightweight and strong materials, but many of them are difficult to chemically treat. This is because high-tensile steel sheets have a thick oxide film, and the reactivity to chemical conversion treatment agents is reduced due to alloy elements such as C, Si, and Mn contained in the high-tensile steel sheets. For this reason, the formation of the cationic electrocoating film after the chemical conversion treatment is adversely affected, and it is desired to obtain sufficient corrosion resistance after the cationic electrocoating.
[0006] The present invention has been made in view of the above, and has an object to provide a method for pre-painting treatment of an automobile body including a high-tensile steel sheet, which can provide favorable corrosion resistance after painting. [Means for solving the problem]
[0007] (1) The present invention relates to a method for pre-painting treatment of an automobile body, which comprises carrying out an alkaline degreasing step, a first water-rinsing step, a chemical conversion treatment step, a second water-rinsing step, and a cationic electrodeposition coating step in this order, and the chemical conversion treatment agent used in the chemical conversion treatment step contains zirconium (A), free fluorine ions (B), an allylamine-diallylamine copolymer (C), aluminum ions (D), and nitrate ions (E), the concentration of the zirconium (A) being 50 to 500 ppm by mass in terms of metal element, the concentration of the free fluorine ions (B) being 5 to 30 ppm by mass, and the content ratio of diallylamine segments derived from diallylamine in the allylamine-diallylamine copolymer (C) being 50 to 500 ppm by mass in terms of metal element, and the content ratio of diallylamine segments derived from allylamine being 50 to 500 ppm by mass in terms of metal element, and the content ratio of allyl ... the allylamine-diallylamine copolymer (C) has a weight average molecular weight of 5,000 to 100,000 and a concentration of 100 to 350 ppm by mass in terms of resin solids concentration; the allylamine-diallylamine copolymer (C) is an acid addition salt having an anionic counter ion, and the pKa of an acid forming the acid addition salt is within a range of -3.7 to 4.8; the aluminum ion (D) has a concentration of 90 to 500 ppm by mass; and the nitrate ion (E) has a concentration of 2,000 to 13,000 ppm by mass.
[0008] (2) The method for pretreatment of an automobile body for painting according to (1), wherein the chemical conversion treatment agent has a pH of 3.5 to 5.5.
[0009] (3) In the coating film on the surface of a high-tensile steel sheet formed by the method for pre-painting an automobile body according to (1) or (2), the concentration of the zirconium (A) is 20 to 200 mg / m in terms of metal element. 2The automobile body is made of materials including high tensile steel plate with a coating. Effect of the Invention
[0010] According to the present invention, there is provided a method for pre-painting treatment of an automobile body including a high-tensile steel plate, which can provide favorable corrosion resistance after painting. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to the description of the following embodiments.
[0012] <Pre-painting method for automobile bodies> The paint pretreatment method for an automobile body according to this embodiment involves carrying out an alkaline degreasing process, a first water rinsing process, a chemical conversion treatment process, a second water rinsing process, and a cathodic electrodeposition coating process, in that order, on an automobile body made of materials including high-tensile steel plate.
[0013] (Alkaline degreasing process) The alkaline degreasing step is a step in which the high-tensile steel plate of an automobile body, which is the object to be treated, is immersed in a degreasing agent such as a phosphorus-free and nitrogen-free degreasing cleaning solution for a few minutes at, for example, 30 to 55° C. A preliminary degreasing treatment may be performed prior to the alkaline degreasing step.
[0014] (1st water washing process) The first water washing step is a step of washing off the degreaser after the alkaline degreasing step, and is performed by spraying a large amount of washing water once or a plurality of times.
[0015] (chemical conversion treatment process) The chemical conversion treatment process is a process of forming a chemical conversion coating on the surface of a high-tensile steel sheet of an automobile body to produce a surface-treated steel sheet. The chemical conversion coating formation process is carried out by contacting a chemical conversion treatment agent with the surface of the high-tensile steel sheet. The contact method is not particularly limited, and examples thereof include a dipping method, a spraying method, and a roll coating method. The treatment temperature in the chemical conversion treatment process can be in the range of 20 to 70°C, and preferably in the range of 30 to 50°C. The treatment time in the chemical conversion treatment process can be in the range of 5 to 1200 seconds, and preferably in the range of 30 to 120 seconds. The composition of the chemical conversion treatment agent used in the chemical conversion treatment process will be described in detail later.
[0016] (2nd water washing process) The second water-rinsing step is performed by performing spray treatment or immersion water-rinsing once or multiple times within a range that does not affect adhesion and corrosion resistance after painting. The final water-rinsing step is preferably performed with ion-exchanged water or pure water. After the second water-rinsing step, a step of drying the surface-treated steel sheet may be provided as necessary.
[0017] (Cation electrodeposition coating process) The cationic electrodeposition coating process is a process in which the surface-treated steel sheet produced by the above-mentioned chemical conversion treatment process is cationic electrodeposition coated to form an electrodeposition coating film on the surface. The cationic electrodeposition paint used in the cationic electrodeposition coating is not particularly limited, and a conventionally known cationic electrodeposition paint made of aminated epoxy resin, aminated acrylic resin, sulfonated epoxy resin, etc. can be used. The cationic electrodeposition coating method using the above-mentioned cationic electrodeposition paint is not particularly limited, and a known cationic electrodeposition coating method can be applied.
[0018] <Chemical conversion coating agent> The chemical conversion treatment agent according to this embodiment can form a chemical conversion coating that provides favorable corrosion resistance after cathodic electrodeposition coating on the surface of a high-tensile steel plate that constitutes an automobile body.
[0019] The chemical conversion treatment agent according to this embodiment contains zirconium (A), free fluorine ions (B), an allylamine-diallylamine copolymer (C), aluminum ions (D), and nitrate ions (E).
[0020] (Zirconium(A)) Zirconium (A) is a chemical conversion coating component. The formation of a chemical conversion coating containing zirconium (A) on the surface of a high-tensile steel sheet can improve the corrosion resistance and abrasion resistance of the high-tensile steel sheet, and can also improve adhesion to a cationic electrocoating film.
[0021] The source of the zirconium (A) is not particularly limited, but examples thereof include alkali metal fluorozirconates such as KZrF6, hydrofluoric acid (HZrF6), ammonium hexafluorozirconate ((NH4)2ZrF6), ammonium zirconium carbonate ((NH4)2ZrO(CO3)2), tetraalkylammonium-modified zirconium, zirconium fluoride, and zirconium oxide.
[0022] The concentration of the zirconium (A) is 50 to 500 ppm by mass in terms of the metal element. If the concentration of zirconium (A) is less than 50 ppm, the resulting chemical conversion coating film will not have sufficient performance. If the concentration of zirconium (A) exceeds 500 ppm by mass, no further effect will be obtained, which is economically disadvantageous. From the above viewpoints, the concentration of the zirconium (A) is preferably 100 to 500 ppm by mass in terms of the metal element.
[0023] (Free fluoride ion (B)) The free fluorine ion (B) has a function of etching the surface of the metal substrate. The source of the free fluorine ion (B) is not particularly limited, and examples thereof include fluorides such as hydrofluoric acid, ammonium fluoride, fluoroboric acid, ammonium hydrogen fluoride, sodium fluoride, and sodium hydrogen fluoride. In addition, examples of complex fluorides include hexafluorosilicate, and specific examples thereof include hydrosilicic acid, zinc hydrosilicic acid, manganese hydrosilicic acid, magnesium hydrosilicic acid, nickel hydrosilicic acid, iron hydrosilicic acid, and calcium hydrosilicic acid. In addition, fluorine-containing compounds such as alkali metal fluorozirconates exemplified as the source of zirconium (A) can be a source of zirconium (A) and also a source of free fluorine ion (B).
[0024] The concentration of the free fluorine ion (B) is 5 to 30 ppm by mass in terms of elemental fluorine. If the concentration of the free fluorine ion (B) is less than 5 ppm by mass, etching is insufficient and a good chemical conversion film cannot be obtained. If the concentration exceeds 30 ppm by mass, etching is excessive and a chemical conversion film cannot be formed satisfactorily. The concentration of the free fluorine ion (B) can be measured, for example, by a commercially available fluorine ion meter (for example, IM-32P, manufactured by DKK Toa Corporation).
[0025] (Allylamine-diallylamine copolymer (C)) The allylamine-diallylamine copolymer (C) has at least both a segment derived from allylamine and a segment derived from diallylamine (hereinafter sometimes referred to as an "allylamine segment" or "diallylamine segment") as structural units. Each of the above segments may be independently in a quaternized state. Each of the above segments may independently have a counter ion.
[0026] In the allylamine-diallylamine copolymer (C) of the present embodiment, the diallylamine segment content is 80 mol% or more and 98 mol% or less. The diallylamine segment content is defined as the mol% of the diallylamine segment relative to the total of the allylamine segment and the diallylamine segment in the allylamine-diallylamine copolymer (C). If the diallylamine segment content is less than 80 mol%, sufficient corrosion resistance after coating cannot be obtained. If the diallylamine segment content is more than 98 mol%, the adhesion of the chemical conversion coating to the coating film decreases. From the above viewpoint, the diallylamine segment content is preferably 90 mol% or more and 98 mol% or less. Examples of the diallylamine segment include heterocyclic structures represented by the following general formulas (1a) and (1b). The heterocyclic structure may be a saturated heterocyclic structure.
[0027] [ka] (In the above formula, R 1 represents a hydrogen atom, an alkyl group, or an aralkyl group.
[0028] The allylamine segment in the allylamine-diallylamine copolymer (C) is, for example, represented by the following general formula (2).
[0029] [ka]
[0030] The allylamine-diallylamine copolymer (C) is an acid addition salt having an anionic counter ion for an ammonium cation. The dissociation constant pKa of the acid forming the acid addition salt is within the range of -3.7 to 4.8. In this specification, the dissociation constant pKa of the acid means a value when the solvent is water and the temperature is 25°C. The diallylamine segment constituting the allylamine-diallylamine copolymer (C) which is the acid addition salt is, for example, represented by the following general formulas (1c) and (1d). [ka] (In the formula, R 2 and R 3 is a hydrogen atom, an alkyl group or an aralkyl group, D - indicates a monovalent anion.)
[0031] The anionic counter ion is not particularly limited, and examples thereof include monovalent anions, such as carboxylate ions (e.g., formate ion, acetate ion, benzoate ion), chloride ion, sulfate ion, nitrate ion, etc. Examples of acids that form acid addition salts include organic acids (e.g., formic acid, acetic acid, benzoic acid), and inorganic acids (e.g., hydrochloric acid, sulfuric acid, nitric acid).
[0032] The allylamine-diallylamine copolymer (C) may have a segment derived from allylamine or a segment other than the diallylamine segment, as required. For example, the segment derived from N,N-dialkylaminoalkyl(meth)acrylate and its salt or quaternized product, N,N-dialkylaminoalkyl(meth)acrylamide and its salt or quaternized product, vinylimidazole and its salt or quaternized product, vinylpyridine and its salt or quaternized product, N-alkylallylamine and its salt, N,N-dialkylallylamine and its salt, N-alkyldiallylamine and its salt or quaternized product, etc. may be mentioned.
[0033] The allylamine-diallylamine copolymer (C) may further have a segment other than those mentioned above, if necessary, for example, a segment derived from sulfur dioxide, an unsaturated compound having a hydroxy group such as 2-hydroxyethyl (meth)acrylate, an alkyl (meth)acrylate ester such as methyl (meth)acrylate or ethyl (meth)acrylate, a vinyl carboxylate such as vinyl acetate or vinyl propionate, an unsaturated acid, or a (meth)acrylamide.
[0034] The concentration of the allylamine-diallylamine copolymer (C) is 100 to 350 ppm by mass in terms of resin solids concentration. If the concentration is less than 100 ppm by mass, sufficient adhesion of the chemical conversion coating cannot be obtained. If the concentration exceeds 350 ppm by mass, the formation of the chemical conversion coating may be inhibited. From the above viewpoints, the concentration of the allylamine-diallylamine copolymer (C) is preferably 125 to 300 ppm by mass in terms of resin solids concentration.
[0035] The weight average molecular weight of the allylamine-diallylamine copolymer (C) is 5,000 to 100,000. If the weight average molecular weight is less than 5,000, sufficient adhesion of the chemical conversion coating cannot be obtained. If the weight average molecular weight exceeds 100,000, the formation of the chemical conversion coating may be inhibited. From the above viewpoints, the weight average molecular weight of the allylamine-diallylamine copolymer (C) is preferably 20,000 to 100,000.
[0036] The weight average molecular weight of the allylamine-diallylamine copolymer (C) can be measured, for example, by gel permeation chromatography (GPC). For example, a Hitachi L-6000 high-performance liquid chromatograph can be used as the measuring device, with a Hitachi L-6000 eluent flow pump, a Shodex RI SE-61 differential refractive index detector as the detector, and Asahi Pack's aqueous gel filtration type GS-220HQ (molecular weight exclusion limit 3,000) and GS-620HQ (molecular weight exclusion limit 2 million) columns connected in double. An example of the GPC measurement method is shown below. The sample is adjusted to a concentration of 0.5 g / 100 ml with the eluent, and 20 μl is used. A 0.4 mol / L aqueous sodium chloride solution is used as the eluent. The column temperature is 30°C, and the flow rate is 1.0 ml / min. A calibration curve is obtained using polyethylene glycols with molecular weights of 106, 194, 440, 600, 1470, 4100, 7100, 10300, 12600, and 23000 as standard samples. The weight average molecular weight (Mw) of the copolymer is obtained based on the above calibration curve.
[0037] The allylamine-diallylamine copolymer (C) may be modified within the scope of the present invention. For example, some of the amino groups of the allylamine-diallylamine copolymer (C) may be modified by a method such as acetylation, or the copolymer may be crosslinked with a crosslinking agent to the extent that the solubility is not affected.
[0038] The method for preparing the allylamine-diallylamine copolymer (C) is not particularly limited, but may be, for example, a method in which a mixture of monomers, which is allylamine, diallylamine, and other components as necessary, is radically polymerized in a suitable solvent in the presence of a radical polymerization initiator. The polymerization conditions may be appropriately selected from conditions known to those skilled in the art.
[0039] (Aluminum ion (D)) The aluminum ion (D) contained in the chemical conversion treatment agent can further improve the corrosion resistance after cationic electrodeposition coating. The source of the aluminum ion (D) is not particularly limited, and examples thereof include aluminum oxide, hydroxide, fluoride, chloride, sulfate, nitrate, borate, carbonate, and organic acid salt. The concentration of the aluminum ion (D) is 90 to 500 ppm by mass, and preferably 90 to 350 ppm by mass.
[0040] (Nitrate ion (E)) The nitrate ion (E) acts as an oxidizing agent for accelerating the reaction of forming the chemical conversion film. Sources of the nitrate ion (E) include the above-mentioned aluminum nitrate and the nitrate ion which is the anionic counter ion of the allylamine-diallylamine copolymer (C), as well as nitric acid, sodium nitrate, potassium nitrate, ammonium nitrate, etc. The concentration of the nitrate ion (E) is 2000 to 13000 ppm by mass, and preferably 3000 to 12000 ppm by mass.
[0041] (Other Ingredients) The chemical conversion treatment agent according to the present embodiment preferably further contains a silane coupling agent. By containing a silane coupling agent in the chemical conversion treatment agent, the coating film adhesion of the chemical conversion coating can be further improved. The silane coupling agent is not particularly limited, but is preferably one or more silane coupling agents selected from the group consisting of, for example, amino group-containing silane coupling agents, epoxy group-containing silane coupling agents, hydrolysates of amino group-containing silane coupling agents, hydrolysates of epoxy group-containing silane coupling agents, polymers of amino group-containing silane coupling agents, and polymers of epoxy group-containing silane coupling agents.
[0042] The amino group-containing silane coupling agent is not particularly limited, and examples thereof include known silane coupling agents such as N-2(aminoethyl)3-aminopropylmethyldimethoxysilane, N-2(aminoethyl)3-aminopropyltrimethoxysilane, N-2(aminoethyl)3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, and N,N-bis[3-(trimethoxysilyl)propyl]ethylenediamine. Commercially available amino group-containing silane coupling agents such as KBM-602, KBM-603, KBE-603, KBM-903, KBE-9103, and KBM-573 (all manufactured by Shin-Etsu Chemical Co., Ltd.), and XS1003 (manufactured by Chisso Corporation) can also be used.
[0043] The epoxy group-containing silane coupling agent is not particularly limited, and examples thereof include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyldiethylethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 5,6-epoxyhexyltriethoxysilane, etc. Commercially available agents such as "KBM-403", "KBE-403", "KBE-402", and "KBM-303" (all manufactured by Shin-Etsu Chemical Co., Ltd.) can also be used.
[0044] The chemical conversion treatment agent according to the present embodiment may contain components other than those described above. For example, it is preferable to further contain zinc as a chemical conversion coating component. This can further improve the corrosion resistance of the metal substrate on which the chemical conversion coating is formed. In addition to the above, the chemical conversion coating component may contain at least one metal component selected from the group consisting of magnesium, calcium, gallium, indium, and copper. In addition, metal components of manganese, iron, and cobalt may be contained. The supply source of the above-mentioned coating component is not particularly limited, and examples thereof include oxides, hydroxides, fluorides, chlorides, sulfates, nitrates, borates, carbonates, and organic acid salts of each metal.
[0045] It is preferable that the chemical conversion treatment agent according to this embodiment is substantially free of phosphate ions. In this specification, "substantially free of phosphate ions" means that phosphate ions are not contained to an extent that they act as a component in the chemical conversion treatment agent. Since the chemical conversion treatment agent according to this embodiment is substantially free of phosphate ions, phosphorus, which is a cause of environmental load, is not substantially used. In addition, the generation of sludge such as iron phosphate and zinc phosphate that occurs when using a zinc phosphate treatment agent can be suppressed.
[0046] (pH) The chemical conversion treatment agent preferably has a pH of 3.5 to 5.5. If the pH is less than 3.5, etching is excessive and a sufficient chemical conversion film cannot be formed. If the pH is more than 5.5, etching is insufficient and a good chemical conversion film cannot be obtained. From the above viewpoints, the pH is more preferably 4.0 to 4.5. In order to adjust the pH of the chemical conversion treatment agent, acidic compounds such as nitric acid and sulfuric acid, and basic compounds such as sodium hydroxide, potassium hydroxide, and ammonia can be used.
[0047] <Automobile body made of materials including high-tensile steel plates> The chemical conversion coating film is formed on the surface of an automobile body made of a material including a high-tensile steel plate by the chemical conversion coating agent according to the present embodiment. The chemical conversion coating agent according to the present embodiment can impart sufficient corrosion resistance to high-tensile steel plates to which conventional chemical conversion coating agents have difficulty imparting sufficient corrosion resistance. The high-tensile steel plate means a steel plate having a tensile strength equal to or greater than a certain level. Examples of high-tensile steel plates include high-tensile hot-rolled steel plates, high-tensile cold-rolled steel plates, and high-tensile galvanized steel plates.
[0048] At least a part of the automobile body as a coating object to be treated by the automobile body painting pretreatment method of the present embodiment is made of high tensile steel sheet. The automobile body may be entirely made of high tensile steel sheet, or may have a part made of high tensile steel sheet and a part made of steel sheet other than high tensile steel sheet. Examples of steel sheets other than high tensile steel sheet that can be used to form the coating object include cold rolled steel sheet, hot rolled steel sheet, stainless steel, zinc or zinc-based alloy plated steel sheet, etc. Examples of zinc or zinc-based alloy plated steel sheet include zinc-based electroplated, hot-dip plated, and vapor deposition plated steel sheets such as zinc-plated steel sheet, zinc-nickel plated steel sheet, zinc-iron plated steel sheet, zinc-chromium plated steel sheet, zinc-aluminum plated steel sheet, zinc-titanium plated steel sheet, zinc-magnesium plated steel sheet, and zinc-manganese plated steel sheet.
[0049] In the automobile body made of a material including the high tensile steel plate according to the present embodiment, the content of zirconium (A) in the coating formed on the surface of the high tensile steel plate by the chemical conversion treatment agent is 20 to 200 mg / m2 in terms of metal element. 2 It is preferable that the content of the metal component (A) is 20 mg / m 2 If the content of the metal component (A) is less than 200 mg / m, a uniform chemical conversion coating cannot be obtained. 2 If the amount exceeds this range, no further effect can be obtained, which is economically disadvantageous. EXAMPLES
[0050] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the description of the following examples.
[0051] Example 1 A commercially available cold-rolled high-tensile steel plate (7 cm x 15 cm x 0.1 cm, manufactured by Standard Test Piece Co., Ltd.) was used as the substrate, and surface treatment was performed under the following conditions.
[0052] In the alkaline degreasing process, the substrate was immersed in 2% by mass of "Surf Cleaner EC90" (a degreasing agent manufactured by Nippon Paint Surf Chemicals Co., Ltd.) at 40°C for 2 minutes. In the first water washing process, tap water was sprayed for 30 seconds. In the chemical conversion treatment process, zirconic acid hydrofluoric acid, acidic sodium fluoride, allylamine-diallylamine copolymer (allylamine segment: 20 mol%, diallylamine segment: 80 mol%, weight average molecular weight 5000, acetic acid (pKa 4.8) salt), aluminum nitrate nonahydrate, and sodium nitrate were used to prepare a chemical conversion treatment agent, as shown in Table 1, so that the concentration of Zr was 50 ppm by mass in terms of metal element, the concentration of free fluorine ions was 15 ppm by mass, and the concentration of allylamine-diallylamine copolymer was 100 ppm by mass in terms of resin solids concentration. The pH was adjusted to 4.0 using sodium hydroxide. The temperature of the chemical conversion treatment agent was adjusted to 40°C, and the substrate was immersed for 120 seconds.
[0053] In the second water washing step, the plate was sprayed with tap water for 30 seconds. Then, it was sprayed with ion-exchanged water for another 30 seconds. Then, it was dried at 80°C for 5 minutes in an electric drying oven. The zirconium content (mg / m2) in the chemical conversion coating was measured using a "ZSX PrimusII" (X-ray analyzer manufactured by Rigaku Corporation). 2 ) were measured and are shown in Table 1.
[0054] For the cationic electrocoating film formation process, cationic electrocoating was performed using "Powernics 1050" (a cationic electrocoating paint manufactured by Nippon Paint Automotive Coatings Co., Ltd.) so that the dry film thickness was 20 μm. After rinsing with water, the plate was baked by heating at 170°C for 20 minutes to prepare the test plate of Example 1.
[0055] (Examples 2 to 11, Comparative Examples 1 to 13) Test panels of the above-mentioned Examples and Comparative Examples were prepared in the same manner as in Example 1, except that the composition of the chemical conversion treatment agent in the chemical conversion treatment step was as shown in Table 1. The detailed composition of the chemical conversion treatment agents of the above-mentioned Examples and Comparative Examples is as follows.
[0056] The allylamine-diallylamine copolymer (C) used in the following Examples and Comparative Examples was the commercially available product shown below. In Comparative Example 9, a diallylamine copolymer was used instead of the allylamine-diallylamine copolymer (C). Example 3, Comparative Example 5: "PAA-D19-A", Examples 8, 10, and Comparative Example 1: "PAA-D19-HCL", Comparative Example 7: "PAA-D41-HCl", Comparative Example 8: "PAA-D11-HCl", Comparative Example 9: "PAS-21" (all manufactured by Nittobo Medical Co., Ltd.) In the examples and comparative examples, hydrochloric acid was used as the additional acid having a pKa of -3.7.
[0057] [Peeling test after saltwater / hot water test (SDT)] After making cross cuts reaching the substrate on the test plates of the examples and comparative examples, they were immersed in a 5% by mass NaCl aqueous solution at 55°C for 240 hours. They were then rinsed with tap water and further dried at room temperature. Thereafter, a Cellophane Tape (registered trademark) peel test was conducted on the cross cut portion of the electrodeposition coating film, and the maximum peel width on one side from the cross cut was measured. Evaluation was performed according to the following criteria, with 2 or more being considered a pass. The results are shown in Table 1. 3: Less than 1.0mm 2: 1.0mm or more and less than 2.5mm 1: 2.5mm or more
[0058] [Total area of general surface blisters after saltwater test (SDT)] For the test plates of the examples and comparative examples, the electrodeposition coated plates were immersed in a 5% by mass NaCl aqueous solution at 55°C for 240 hours. Then, they were washed with tap water and further dried at room temperature. Thereafter, the total area ratio of blisters that occurred on the general surface of the electrodeposition coating film was measured. Evaluation was performed according to the following criteria, with 3 or more being considered as passing. The results are shown in Table 1. 3:0% 2: More than 0% and less than 1.0% 1:1.0% or more
[0059] [Combined Cyclic Corrosion Test (CCT)] The test plates of the examples and comparative examples were subjected to a cyclic corrosion test after making cross cuts reaching the substrate. The test method was a cyclic corrosion test under the following conditions, which was counted as one cycle, and 50 cycles were performed. Humidity 40℃95%RH, 2 hours Salt spray 35℃5%NaCl, 2 hours Drying: 60℃, 1 hour Humidity 50℃95%RH, 6 hours Drying: 60℃, 2 hours Humidity 50℃95%RH, 6 hours Drying: 60℃, 2 hours Low temperature -20℃, 3 hours
[0060] After the CCT test, the maximum bulge width on both sides from the cut part was measured. Evaluation was performed according to the following criteria, with a score of 3 or higher being considered a pass. The results are shown in Table 1. 4: Less than 3.0mm 3: 3.0mm or more and less than 3.5mm 2: 3.5mm or more and less than 4.0mm 1:4.0mm or more
[0061] [Table 1]
[0062] From the results in Table 1, it was confirmed that the chemical conversion treatment agents according to the respective Examples provided preferable corrosion resistance after cationic electrodeposition coating, compared with the chemical conversion treatment agents according to the comparative examples.
Claims
1. A paint pretreatment method for an automobile body, comprising carrying out an alkaline degreasing step, a first water washing step, a chemical conversion treatment step, a second water washing step, and a cathodic electrodeposition coating step in this order, The chemical conversion treatment agent used in the chemical conversion treatment step is Zirconium (A), Free fluorine ions (B); An allylamine-diallylamine copolymer (C); Aluminum ions (D), and nitrate ions (E), The concentration of the zirconium (A) is 50 to 500 ppm by mass in terms of metal element, The concentration of the free fluorine ions (B) is 5 to 30 ppm by mass, the content ratio of the diallylamine segment derived from diallylamine in the allylamine-diallylamine copolymer (C) is 80 mol % or more and 98 mol % or less based on the total content of the allylamine segment derived from allylamine and the diallylamine segment, The allylamine-diallylamine copolymer (C) has a weight average molecular weight of 5,000 to 100,000 and a resin solids concentration of 100 to 350 ppm by mass, the allylamine-diallylamine copolymer (C) is an acid addition salt having an anionic counterion, and the pKa of the acid forming the acid addition salt is within the range of −3.7 to 4.8; The concentration of the aluminum ions (D) is 90 to 500 ppm by mass, The method for pre-painting treatment of an automobile body made of a material including a high-tensile steel plate, wherein the concentration of the nitrate ions (E) is 2,000 to 13,000 ppm by mass.
2. 2. The method for pre-painting treatment of an automobile body according to claim 1, wherein the chemical conversion treatment agent has a pH of 3.5 to 5.5.
Citation Information
Patent Citations
Chemical conversion treatment agent and surface-treated metal
JP2004218074A
Surface treatment composition for metal, surface treatment liquid for metal, surface treatment method for metal, and metallic material
JP2005264230A
Paint pretreatment agent for coating-type paint, and coating-type painting method
JP2013087312A
Metal surface treatment agent, metal surface treatment method, and metal material
WO2018207384A1
Cited By
Chemical conversion coating agent, surface-treated metal and surface treatment method
JPWO2024135605A1
